Bayesian modeling of social network data - Ansari, Asim (Henry Stewart Talks, 2010)
Social networks, Some modeling questions and issues in social network research, Nature of network data, Network structure and heterogeneity, Statistical models of network structure, Sender and receiver effect, Selectivity and reciprocity, Bayesian estimation, Schema of a social network, Swiss online social network of music